MATHEMATICAL APPROACH FOR RECOVERING ENCRYPTION KEYOF STREAM CIPHER SYSTEM - Radhi, Abdul Kareem (Iraqi Journal of Science, 2024)
Stream cipher system plays an important role in many practical encryption systems.Moreover it can be an ideal source in random number generation. Shift registers arethe backbone of such systems. This paper presents a method for attacking and recoveringthe basic key for the general stream cipher systems. Different criteria should be studiedcarefully when a key stream generated via these systems.Depending on the type of feedback connection of different stages, the output stream maybe classified as linear and nonlinear. Different parameters specify complexity degree ofthe output of these systems. Proposed system achieved to recover the initial cipher keyvia two modules. The First module focuses on simulating some general stream ciphersystems including shift registers with different lengths, while the second recovers thebasic or the initial key which is generated from the first module. Recovering keyattached by normalizing polynomial equations to set of linear equations. Nonlinearityoutput normalized to linear equation before recovering the key. The proposed techniqueovercomes the complexity parameter of linear and nonlinear stream sequence comparedwith other techniques in this field. C++ version 4.5 where used in implementing theproposed system.